VD_FINDINFO 178/2009/JKR vom 4. Dezember 2009 - VD Tribunal cantonal (2009)
MANDAT, GESTION DE FORTUNE, GARANTIE BANCAIRE, RESPONSABILITÉ CONTRACTUELLE | 11. al. 1 CO, 16 al. 1 CO, 321e CO, 394 CO, 397 CO, 398 CO, 97 CO, 1 LDIP, 116 LDIP, 117 LDIP, 5 LDIP